The influence of COMT gene functional polymorphism on formation of chronic pain - Byś, Aleksandra; Zieliński, Grzegorz; Filipiak, Zuzanna; Ginszt, Michał (Journal of Education, Health and Sport, 2019)
Introduction and purpose The prevalence of chronic pain is estimated at around 30% of the world’s population. The risk of developing chronic pain depends, among others, on from genetic factors. Considering that chronic pain is a serious diagnostic and therapeutic problem, and if treated inadequately constitutes a serious threat to public health, focus should be on identifying the risk factors for its occurrence in order to establish an effective treatment. The aim of the work is to summarize the latest knowledge about the influence of functional polymorphism of the COMT gene on the formation of chronic pain. Material and methods The material for this literature review were publications on the subject of research from the last 5 years. Relevant articles have been identified by two authors using PubMed, Google Scholar and Researchgate publishing bases using key words: "gene COMT", "headache", "chronic pain", "chronic back pain", "fibromyalgia", "temporomandibular disorder", "postoperative pain" according to Medical Subject Headings. The review of articles consisted of 3 stages. Finally, 19 works were qualified for the review. Results Functional polymorphism of the COMT gene is one of the factors affecting the modulation of pain. Its single genetic variants will positively correlate with the occurrence of temporomandibular disorders and chronic lower back pain. Differences in genetic variants of the COMT gene will also affect the susceptibility to fibromyalgia and increase the severity of clinical symptoms. The COMT gene polymorphism does not seem to correlate with chronic headaches. Conclusions Research to determine the effect of COMT gene polymorphism can significantly affect the diagnosis and treatment of chronic pain.